Energy Poverty and Labor Supply in Eastern Indonesia - Hana Dwi Kristanti; Djoni Hartono; Suhendra (Economics Development Analysis Journal, 2024)
Gender inequality in economic participation is a crucial aspect of sustainable development strategies aimed at improving living standards. The high level of inequality is primarily driven by stagnation in female labor supply. One of the factors influencing labor supply is energy povertyIn Indonesia, studies addressing the relationship between energy poverty and economic participation remain scarce. Therefore, this research aims to fill the existing research gap by analyzing the relationship between energy poverty and labor supply, particularly in Eastern Indonesia. To address endogeneity issues caused by selection bias, this study employs the Two-Step Heckman method. Using data from the 2021 Susenas, the findings reveal that energy poverty significantly reduces working hours in Eastern Indonesia. This impact is more pronounced among male workers compared to female workers and is more dominant in urban areas than in rural areas. These findings underscore the importance of policy interventions aimed at reducing energy poverty as a means of improving labor productivity, particularly in Eastern Indonesia. This study also contributes to understanding the dynamics of labor markets in regions facing energy and economic development challenges.